Promoting resilience in vulnerable populations: focus on opioid-exposed children, siblings of children with special healthcare needs and support for children through school-based interventions. Issue 1 (February 2019) - Brodie, Nicola; Keim, Jennifer L.; Silberholz, Elizabeth A.; Spector, Nancy D.; Pattishall, Amy E.
Abstract : Purpose of review: Resilience is an important factor in withstanding the health consequences of childhood adversity. This article discusses recent literature related to promoting resilience in opioid-exposed children and siblings of children with special healthcare needs. It also addresses ways that school systems can foster childhood resilience. Recent findings: Rising rates of opioid-exposed newborns have necessitated the development of multiple strategies to address the medical and social needs of this vulnerable pediatric population. Siblings of children with special healthcare needs are a growing but sometimes overlooked group who have unique challenges that can be supported by healthcare providers. School programs that reward positive behavior and encourage self-regulation through activities like physical activity and mindfulness can foster an environment for improved youth resiliency. Summary: New research has led to the development of resources that help pediatric providers assess the needs of their vulnerable patient populations and foster resilience through attention to these patients' medical, emotional and social needs. Patients benefit from national policy efforts and local school programs that each promote resilience.